(untitled) (International Journal of Applied Sciences and Biotechnology, 2025)
Goat farming holds significant importance in Nepal due to goats’ adaptability to diverse climatic zones, ease of rearing, and their contribution as a sustainable source of income. However, the sustainability of goat farming depends greatly on the production and management practices followed by farmers. This study was conducted in Budhiganga and Triveni Municipalities of Bajura district to assess the demographic characteristics of goat farmers and the production systems they follow. A door-to-door survey of 129 households was conducted to gather information on housing, feeding, breeding, health, and marketing practices. The results showed that agriculture was the main source of income for 75.2% of respondents. The average goat herd size was 8.98 ± 0.522. Most farmers used a semi-intensive housing system with ground-level flooring, adequate ventilation, and drainage. Fodder availability throughout the year was found to be insufficient. Colostrum feeding to newborn kids was a common practice. Crossbreeding was preferred over inbreeding, and mating was generally done after estrus detection. Only 3.9% of farmers practiced isolation and quarantine for new or sick animals. Many farmers reported using deworming and vaccination, and 44.2% practiced dipping to control external parasites. Furthermore, 96.1% of farmers had knowledge of safe carcass disposal and usually buried dead animals in the field. In terms of marketing, goats were mostly sold directly to buyers at any time of the year, not specifically during festivals like Dashain. The study highlights the current farming practices and can inform policymakers in designing effective strategies to improve goat farming and farmer livelihoods. Int. J. Appl. Sci. Biotechnol. Vol 13(2): 74-80.